M&A effects on shareholders' wealth within South African REITs - Magazi, Mthokozisi W (My University, 2020)
Mergers and Acquisitions (M&A) within real estate investments trusts (REITs) have been a way to; catalyse growth, improve the competitiveness, broaden portfolio to reduce business risk, maintain competitiveness and increase shareholders wealth. This research is to examine whether M&As impact the performance of South African listed REITs. Also, the research will seek to analyse the performance of REITs in general. Upon their formalization there has been a substantial growth in the return of REITs. Shareholders seek to maximize returns and M&As create abnormal returns in the short-run. Nonetheless, M&As underperform in the long-run. The hubris theory suggests that CEOs and managers tend to make decisions based on their own bias of being overoptimistic when evaluating M&A opportunities. Real estate transactions are unique in that, most takeovers are friendly transactions. This results in less severe information asymmetry and less government interference. Furthermore, friendly takeovers result in shareholder wealth effect in the short-run. REIT M&A are often large deal sizes and with mixed payments which are often much higher than other payment methods. This study examines 22 REITs M&A during the period April 2013 to December 2019. Moreover, only one transaction per REIT was investigated. Also, the study makes use of the event window methodology to calculate the AR and the CARs. Furthermore, a regression model has been applied to investigate a 41, 11, 7 and 3 day event windows [-20, +20], [-11, +11], [-7, +7] and [-3, +3]. Data was extracted from the companies Stock Exchange News Service (SENS) and Johannesburg Stock Exchange (JSE)
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements of the degree of Masters of Science in Building, 2020 The School of Construction Economics and Management University of Witwatersrand, 2020